153k views
5 votes
Solve the equation A=h(b1+b2) divides by 2 for b1.

User Trevel
by
5.1k points

2 Answers

4 votes
what are the numbers we need to plug in
User MLu
by
5.7k points
6 votes

For this case we have the following equation:


A = \frac {h * (b_ {1} + b_ {2})} {2}

We clear
b_ {1}:

We multiply by 2 on both sides of the equation:


2A = h * (b_ {1} + b_ {2})

We divide between h on both sides:


\frac {2A} {h} = b_ {1} + b_ {2}

We subtract
b_ {2} from both sides of the equation:


b_ {1} = \frac {2A} {h} -b_ {2}

Answer:


b_ {1} = \frac {2A} {h} -b_ {2}

User Youngho
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.